Long-term nitrate response in shallow groundwater to agricultural N regulations in Denmark. (15th June 2019) - Hansen, Birgitte; Thorling, Lærke; Kim, Hyojin; Blicher-Mathiesen, Gitte
Abstract: Over the last 30 years, Denmark has implemented a series of environmental action plans involving regulation of agricultural nitrogen (N) use and management in order to minimize the N pollution of the environment. The local effects of these action plan initiatives depend on various factors such as the efficiency of the implemented measures, and in particular, the hydrogeological structures and geochemical conditions of the subsurface that control the transport and fate of N. In this study, the effects of the Danish agricultural N regulations on shallow oxic groundwater are compared among five small agricultural catchments underlain by two types of lithology (sandy vs. loamy). Long-term spatially dense groundwater monitoring data is compared with monitoring data of nitrate in the root zone leaching and in stream. The results show clear improvements in the environmental state of shallow oxic groundwater in the first two decades since 1989 where the number of monitoring points with significant decreasing nitrate trends gradually increased for both soil types. Such improvements can be attributed to the effects of N mitigation measures implemented as a general regulation all over the country. However, deteriorations have been recorded in the last decade until 2016 where 26–35% of the monitoring points exhibited significant upward nitrate trends in both types of catchments. It is noteworthy that for sandy soils, the major part (93%) of the monitoring points showing significant upward trends in the period 2009–2016, also had concentrations above the groundwater standard of 50 mg/l nitrate in 2016. Altogether, the oxic groundwater in the sandy catchments was more responsive to N regulations than that in the loamy catchments. This might be due to efficient N regulation through statutory norms for the utilization of N in manure, increasing the N use efficiency in areas with a relatively high livestock density. Another reason is the nitrate vulnerability of the aquifers in sandy areas, with widespread oxic conditions from the top soil to the saturated zone. In the loamy catchments, nitrate may be reduced in near-surface localized reduced zones, and the reaction is often fast and the travel time from the root zone to the stream often relatively short. Therefore, stream nitrate concentrations were higher in the loamy catchments than in the sandy catchments. This is attributed to different hydrogeological pathways. Thus, in sandy catchments, deep groundwater is an important pathway, while in loamy catchments tile drains deliver nitrate directly to the streams. Our results indicate that N mitigation measures will help improve groundwater quality in sandy soils, while in loamy soils they will help to reduce surface water N loads. This implies that to achieve optimal environmental N reduction, agricultural N regulations should be strategically implemented according to farming characteristics and site-specific hydrogeological and geochemical conditions of the subsurface. Highlights: Clear nitrate response in shallow groundwater on agricultural N regulation. In sandy sites, groundwater is more responsive to the agricultural N regulations. In sandy sites, groundwater is nitrate vulnerable. In loamy site, surface water is nitrate vulnerable. Target N regulation should be adjusted to hydro-geochemical site characteristics.